K Kesiapan TVRI sebagai Penyelenggara Multipleksing: Peluang dan Hambatan - Nupikso, Daru; Darmanto, Darmanto; Ardison, Ardison (Jurnal Pekommas, 2022)
The policy of migrating from analog television broadcasting systems to digital broadcasting systems resulted in the birth of a new business model with the separation of broadcast operators and multiplexing providers. However, the Television of the Republic of Indonesia (TVRI) has a mandatory task as a broadcast organizer and multiplex operator. This study aims to answer the question, "What are the opportunities and obstacles faced by TVRI as a multiplexing organizer from the aspect of readiness?" The research was conducted using a mixed methods approach, and data collection was carried out through online surveys, document studies, interviews, and participatory action research. The results show that the mandatory task as a multiplexing operator provides a great opportunity for TVRI to obtain a number of financial and non-financial benefits. However, many aspects such as organizational culture, policies, procedures, past experience, organizational structure, and existing HR conditions show performance that is not yet ready to support TVRI's success as a multiplexing operator.